Policies Guiding Pedagogy and Teacher of Business Studies Competency in Kajiado County, Kenya: Instructional Skills’ Policy Discourse - Munyao, Mailo Emmanuel; Amollo, Odundo Paul; Lilian, Ganira Khavugwi (Global Journal of Educational Studies, 2024)
Operative utilization of policies guiding instructional skills is key in shaping ways in which teachers of Business studies incorporate varied methods of teaching, assessment of learning and integration of pedagogical resources for heightening learner academic achievement. Proper formulation and implementation of feasible policies guiding instructional skills possessed by teachers of Business studies tend to ensure even accommodation of learners during instruction process regardless of differences in learning preferences. This study pored over influence of policies directing teaching methods, assessment methods and pedagogical resources employed by teachers of Business studies in Kajiado county; Kenya. The study adopted Descriptive survey design and was informed by Context Evaluation, Input Evaluation, Process Evaluation and Product Evaluation (CIPP) model. A total of 42 respondents from eleven secondary schools in Isinya sub- county were targeted during the study. Data was collected using questionnaires as the main collection tool and interview schedules. The data gathered was ciphered and fed into SPSS software version 25.0 and statistical analysis using inferential and descriptive statistics was done on cross tabulations. The findings revealed that policies on instructional skills were significantly related to teacher competency. Informed by the findings, the study recommends that the Teachers Service Commission (TSC) and Ministry of Education (MoE) should formulate more policies that emphasis on instructional skills which lead teachers of Business studies to accommodate all learners during learning process. Further, the study recommends that the MoE should make teacher training in the country more practical by formulating policies that improve teaching practice period and training institutions to frequent micro teaching sessions, embracing diverse methods of teaching, assessment and guided choice of pedagogical resources.